2022
DOI: 10.1021/acsami.2c03323
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polysaccharide Strengthened Hydrogel Electrolyte and Biopolymer Derived Carbon for Durable Aqueous Zinc Ion Storage

Abstract: Aqueous zinc-ion hybrid supercapacitors (ZHSCs) represent one of the current research subjects because of their flame retardancy, ease of manufacturing, and exceptional roundtrip efficiency. With the evolution into real useful energy storage cells, the bottleneck factors of the corrosion and dendrite growth problems must be properly resolved for largely boosting their cycling life and energy efficiency. Herein, a natural polysaccharide strengthened hydrogel electrolyte (denoted as PAAm/agar/Zn­(CF3SO3)2) was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Additionally, new signals located at 1241, 1161, 1030, and 637 cm −1 can be detected, which correspond to the symmetric CF 3 stretching vibration, asymmetric CF 3 stretching vibration, symmetric SO 3 stretching vibration, and asymmetric SO 3 bending of CF 3 SO 3 − anion, respectively. 34–36 The obtained results suggested that the SPS–Zn hydrogel electrolyte was successfully synthesized.…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, new signals located at 1241, 1161, 1030, and 637 cm −1 can be detected, which correspond to the symmetric CF 3 stretching vibration, asymmetric CF 3 stretching vibration, symmetric SO 3 stretching vibration, and asymmetric SO 3 bending of CF 3 SO 3 − anion, respectively. 34–36 The obtained results suggested that the SPS–Zn hydrogel electrolyte was successfully synthesized.…”
Section: Resultsmentioning
confidence: 85%
“…S65, S66, Table S4, ESI †). 66,[83][84][85][86][87][88] To further examine the real-time influence of environment on the output performance of the CP/EGZn/betaine ZICs in practical application, they were tested in a thermostat with the temperature varying from À40 1C to 80 1C. Intriguingly, the quasi-solid ZICs could endure both low and high temperature tests in turn, and their capacity well recovered when the temperature was set back to 20 1C (Fig.…”
Section: Proof-of-concept Demonstrations Of Environmentally Adaptive ...mentioning
confidence: 99%
“…CP/EGZn/betaine-based ZIC: (c) cycling stability at 2 A g À1 ; (d) capacity and Coulombic efficiency plots at 0.5 A g À1 at different temperatures from À40 1C to 20 1C and from 20 1C to 80 1C. (f) Ragone plot of ZICs in comparison with previously reported ZICs based on different hydrogel electrolytes 66,[83][84][85][86][87][88]. Continuous destructive tests include (e) hammering test, (g) squeezing, rolling, folding, and compressing, and (h) punching and cutting.…”
mentioning
confidence: 96%
“…6e, the energy density of the as-made quasi-solid-state ZHC reaches 113.2 W h kg −1 at a power density of 206.2 W kg −1 , and its power density can be 15 752.4 W kg −1 at 43.8 W h kg −1 , displaying high energy and power outcomes for this flexible device. Moreover, the energy density achieved for our device outstrips that of many other energy-storage systems, such as WC-6ZnN-12U//Zn@CC (27.7 W h kg −1 at 35.7 W kg −1 ), 49 HIWW-based EDLCs (39.1 W h kg −1 at 391 W kg −1 ), 64 P–Co 3 O 4 @P, N–C//Co@P, N–C (47.6 W h kg −1 at 750 W kg −1 ), 65 NPFC 700 -based ZHC (60.1 W h kg −1 at 74.2 W kg −1 ), 66 Zn//PAAm/agar/Zn(CF 3 SO 3 ) 2 //NC (61.3 W h kg −1 at 209.0 W kg −1 ), 67 MoO 2 @NC//CuCo 2 S 4 (65.1 W h kg −1 at 800 W kg −1 ), 68 CNPK-based quasi-solid-state ZHC (89.3 W h kg −1 at 79.0 W kg −1 ), 69 and quasi-solid-state BCF-based ZSC (100.8 W h kg −1 at 400.8 W kg −1 ), 70 (Fig. 6e).…”
Section: Resultsmentioning
confidence: 99%